PELATIHAN AUTOCAD UNTUK PENINGKATAN KOMPETENSI PEMUDA MEMBUAT GAMBAR KERJA RUMAH TYPE 36 DI KELURAHAN RANOTANA WERU - Suriandjo, Hendrik Suryo; Malonda, Ayesha A. L.; Umboh, Karry E. H (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Community Service Activities are part of the Tri Dharma of Higher Education, and Nusantara University of Manado through the Institute for Research and Community Service (LPPM), in 2024 will carry out Community Service for Beginners (PMP) activities with Engineering Graduate Youth Group Partners located in Ranotana Weru Village, Manado City, called the REZA Engineering Youth Group. This partner was chosen because this community group works in the engineering sector but does not yet have permanent employment due to minimal understanding and mastery of the AutoCAD drawing program and only receiving engineering education at the vocational school, D3 and/or college level. This community service activity aims to ensure that partners know and understand the AutoCAD program and improve their ability to operate AutoCAD at an advanced level to design type 36 houses. This activity is carried out in the form of training for partners using the focus group discussion (FGD) method, participant learning center (PCL) through training and participatory action (PA). The results of the training activities can be identified that: 1) an 80% increase in partner knowledge and skills related to AutoCAD, 2) an increase of 92% of partners can operate AutoCAD commands, and 3) an 80% increase in the ability of partners to understand working drawings. The results of these activities concluded that this activity had succeeded in increasing the competence of youth partners in the field of engineering through AutoCAD training to make working drawings of Type 36 houses. Keywords: dedication, AutoCAD, partners, improvement